Think global, act local — and benefit? Impacts of local-authority measures on climate protection - von Seht, Hauke (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
The measures taken by local authorities in the field of climate protection contribute not only to curbing the man-made greenhouse effect. In some cases, these measures also have impacts on the local labour market, on local air quality, or on price stability and the possibility of guaranteeing supply in the energy sector. This article analyses “secondary effects” of this kind and their relevance for the climate-protection policies of local authorities.
Keywords: Article